Ubiquitous IP protocol system - Xu ZHOU; Sheng JIANG; Jie ZHANG; Bo LEI; Xiuli ZHENG; Taixin LI (Dianxin kexue)
Considering the inherent characteristics of the TCP/IP protocol stack are difficult to carry the personalized needs of the future network, based on the development of the network protocol, the next-generation ubiquitous IP (UIP) protocol system was proposed.Ubiquitous IP is a complete set of new network technology system based on IP protocol expansion and “progressive” and “revolutionary” innovation.The key content includes the design concept with flexible IP as the core, the three-dimensional protocol system, and the protocol innovation in the network layer and transport layer IPv6+ and UIP, as two-generation network innovation technologies, can relay the improvement of network capabilities were compared and analyzed.The current progress and future prospect of UIP were summarized.